Analisis Perspektif Influencer Pada Beauty Privilege Dalam Sosial Media Instagram - Niki Anartia; Riska Amaretha; Ridma Meltareza (Institut Nalanda, 2024)
Beauty privilege is a very lively issue being discussed by some people. Many things cite this phenomenon, especially on the social aspect, and one of them is Instagram. The presence of the beauty privilege phenomenon makes people more aware of the importance of maintaining their appearance, both physical body and their appearance, as well as other potential that they have as a human. However, many also say that the phenomenon of beauty privilege triggers unfair treatment in terms of public morality. All of those opinion will be discussed in this journal by qualitative approach using data triangulation with the study of phenomenology theory, literature, and observation with data taken by interview techniques specified by taking samples using purposive sampling techniques on sample triangulation in various fields of work on Instagram social media, namely among influencers, youth, adults, and social media specialists. The results of the discussion show that there is a public view of beauty standards; (1) there is an influence of beauty privilege on careers on social media platforms like Instagram; (2) the importance of having awareness of beauty privilege; and (3) there are deficiencies in the issue of beauty privileges for individuals who have them.